Comparison among three methods for mycobacteria identification - Mondragón-Barreto Misael; Vázquez-Chacón Carlos A.; Barrón-Rivero Candelaria; Acosta-Blanco Patricia; Jost Jr Kenneth C.; Balandrano Susana; Olivera-Díaz Hiram (Instituto Nacional de Salud Pública, 2000)
OBJECTIVE: To compare three methods: Biochemical tests, high-performance liquid chromatography (HPLC) and polymerase chain reaction-restriction fragments length polymorphism (PCR-RFLP), for the identification of mycobacteria, and to perform a cost-benefit analysis to define an optimum identification algorithm. MATERIAL AND METHODS: One-hundred-and-seven mycobacteria isolates were identified by the three methods at Instituto de Diagnóstico y Referencia Epidemiológicos, between February of 1999 and January of 2000 and the results were compared with those of a reference laboratory using the Q-Cochran statistical test. RESULTS: PCR-RFLP was the most rapid and specific procedure but also the most expensive; biochemical tests excelled for identification of Mycobacterium tuberculosis, but were lengthy and expensive for other mycobacteria; HPLC ranked in the middle for price, speed and specificity. CONCLUSIONS: Considering the expected proportion of M. tuberculosis, the following algorithm was proposed: Initially, biochemical tests should be performed; if the results indicate a non-tuberculous mycobacteria, the isolate should be analyzed with HPLC; if results are unclear, the isolate should be analyzed using PCR-RFLP. Isolates showing a previously undescribed PCR-RFLP pattern should be characterized by DNA sequencing.